Globalizacja i kultura jako uwarunkowania marketingowej strategii produktu - Mazurek-Łopacińska, Krystyna (Globalization and Culture: Conditions of the Marketing Product Strategy, 2006)
The article points to the advantages and dangers of the globalization of an economic, political and social character. The dilemma appears: the total marketing or intercultural. The author introduces the premises of the product standardization or their adaptation to local conditions. They are a result of the consumption heterogenization and endeavours to form and manifest the cultural identity of countries and regions. Evaluating the susceptibility of products to the standardization the author points to their differentiation according to relationships with the culture.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 15-27